2006
DOI: 10.1136/hrt.2005.069492
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence of diagnosed atrial fibrillation, its treatment with anticoagulation and predictors of such treatment in UK primary care

Abstract: Objectives: To examine trends in the prevalence of diagnosed atrial fibrillation (AF), its treatment with oral anticoagulants between 1994 and 2003, and predictors of anticoagulant treatment in 2003. Methods: Analysis of electronic data from 131 general practices (about one million registered patients annually) contributing to the DIN-LINK database. Results: From 1994 to 2003 the prevalence of ''active'' AF rose from 0.78% to 1.31% in men and from 0.79% to 1.15% in women. The proportion of patients with AF tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 26 publications
(20 reference statements)
11
95
2
3
Order By: Relevance
“…Therefore the higher estimates in our study were to be expected compared to those from these earlier studies. Our similar prevalence estimates to those of the considerably older Rotterdam study (19) may be explained by the active screening approach for AF in the Rotterdam study which would be expected to outweigh the lower prevalence during the time period of its study conduct (26).…”
Section: Discussionsupporting
confidence: 68%
“…Therefore the higher estimates in our study were to be expected compared to those from these earlier studies. Our similar prevalence estimates to those of the considerably older Rotterdam study (19) may be explained by the active screening approach for AF in the Rotterdam study which would be expected to outweigh the lower prevalence during the time period of its study conduct (26).…”
Section: Discussionsupporting
confidence: 68%
“…In contrast to our results, most studies showed statistically significant reduction in Coumadin use with advanced age. Coumadin usage decreased sharply after 75 years of age (DeWilde et al, 2006). The reason for that difference might be because younger AF patients do not receive Coumadin as commonly as older patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 The prevalence of read-coded AF in 131 GPs in the DIN-LINK database increased from 0.84% to 1.49% in men and from 0.83% to 1.29% in women between 1994 to 2003. 13 Data from the General Practice Research Database showed an overall prevalence of around 1%. 14 The slightly higher prevalence rate in this survey probably relates to the level of elderly population in the catchment area.…”
Section: Discussionmentioning
confidence: 99%